Cardiovascular predictors of mortality and exacerbations in patients with COPD - Alter, Peter; Lucke, Tanja; Watz, Henrik; Andreas, Stefan; Kahnert, Kathrin; Trudzinski, Franziska; Speicher, Tim; Söhler, Sandra; Bals, Robert; Waschki, Benjamin; Welte, Tobias; Rabe, Klaus F.; et al. (Scientific reports, 2022)
In chronic obstructive pulmonary disease (COPD), comorbidities and worse functional status predict worse outcomes, but how these predictors compare with regard to different outcomes is not well studied. We thus compared the role of cardiovascular comorbidities for mortality and exacerbations. Data from baseline and up to four follow-up visits of the COSYCONET cohort were used. Cox or Poisson regression was employed to determine the relationship of predictors to mortality or mean annual exacerbation rate, respectively. Predictors comprised major comorbidities (including cardiovascular disease), lung function (forced expiratory volume in 1 s [FEV1], diffusion capacity for carbon monoxide [TLCO]) and their changes over time, baseline symptoms, exacerbations, physical activity, and cardiovascular medication. Overall, 1817 patients were included. Chronic coronary artery disease (p = 0.005), hypertension (p = 0.044) and the annual decline in TLCO (p = 0.001), but not FEV1 decline, were predictors of mortality. In contrast, the annual decline of FEV1 (p = 0.019) but not that of TLCO or cardiovascular comorbidities were linked to annual exacerbation rate. In conclusion, the presence of chronic coronary artery disease and hypertension were predictors of increased mortality in COPD, but not of increased exacerbation risk. This emphasizes the need for broad diagnostic workup in COPD, including the assessment of cardiovascular comorbidity.
Veröffentlicht: 19. Dezember 2022
Gesehen am 26.07.2023